Microsatellite markers for identification and parentage analysis in the European wild boar (Sus scrofa) - Costa, Vânia (2013)
Background The wild boar (Sus scrofa) is among the most widespread mammal species throughout the old world. Presently, studies concerning microsatellites in domestic pigs and wild boars have been carried out in order to investigate domestication, social behavior and general diversity patterns among either populations or breeds. The purpose of the current study is to develop a robust set of microsatellites markers for parentage analyses and individual identification. Findings A set of 14 previously reported microsatellites markers have been optimized and tested in three populations from Hungary, Portugal and Spain, in a total of 167 samples. The results indicate high probabilities of exclusion (0.99999), low probability of identity (2.0E-13 – 2.5E- 9) and a parentage assignment of 100 %. Conclusions Our results demonstrate that this set of markers is a useful and efficient tool for the individual identification and parentage assignment in wild boars.